2016
DOI: 10.3390/molecules21070820
|View full text |Cite
|
Sign up to set email alerts
|

Justicidin B: A Promising Bioactive Lignan

Abstract: Adverse effects and drug resistance to the current onchopharmacologicals have increased the demand for alternative novel therapeutics. We herein introduce justicidin B, an arylnaphthalen lignan isolated from different plant origins, especially Justicia, Phyllanthus, Haplophyllum and Linum species. This cyclolignan exhibits a wide array of biological properties ranges from piscicidal to antifungal, antiviral and antibacterial activities. Activity against Trypanosoma brucei makes justicidin B a potential antipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 126 publications
1
34
0
Order By: Relevance
“…As described in the Methods and Materials section, fractioning with Sephadex LH-20 of the non-polar extract of P. acuminatus , allowed the isolation of a compound characterized by 1 H-NMR, 13 C-NMR and 2D-(HMBC, HSQC, COSY)-NMR data coincident with reports from the literature [ 37 , 38 , 39 ] on aryl naphthalene lignan Justicidin B ( 20 ) C 21 H 16 O 6 ( Figure 13 ), a metabolite previously reported in P. acuminatus [ 7 ] and extensively studied because of its high antitumoral potential against different cancer cell lines [ 40 ], thus enabling a comparison of bioactivities among this metabolite and the phenolic extract, as described in the following sections.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As described in the Methods and Materials section, fractioning with Sephadex LH-20 of the non-polar extract of P. acuminatus , allowed the isolation of a compound characterized by 1 H-NMR, 13 C-NMR and 2D-(HMBC, HSQC, COSY)-NMR data coincident with reports from the literature [ 37 , 38 , 39 ] on aryl naphthalene lignan Justicidin B ( 20 ) C 21 H 16 O 6 ( Figure 13 ), a metabolite previously reported in P. acuminatus [ 7 ] and extensively studied because of its high antitumoral potential against different cancer cell lines [ 40 ], thus enabling a comparison of bioactivities among this metabolite and the phenolic extract, as described in the following sections.…”
Section: Resultssupporting
confidence: 81%
“…When evaluating the selectivity index (SI), defined as the ratio of IC 50 values of normal cells to cancer cells (AGS or SW620), P. acuminatus extract showed the highest selectivity result for SW620 colon cancer cells (SI = 21.5), followed closely for AGS gastric cancer cells (SI = 20.1), while Justicidin B results showed SI of 5.4 and 4.2 respectively, thus, lower selectivity values than P. acuminatus extract for both AGS and SW620 cancer cell lines. When comparing these selectivity results with reports using similar MTT assay conditions, Justicidin B displayed non-specific cytotoxicity in normal peripheral blood mononuclear cells (PMBC), HepG2 hepatoma, and PC3 prostrate tumor cell lines [ 40 ], while P. niruri phenolic extract showed selectivity values of 2.2 and 2.8, respectively, for AGS gastric and SW colon cancer cells [ 44 ]. Although selectivity (SI ≥ 3) and cytotoxicity (IC 50 ≤ 20) results for P. acuminatus extract on AGS gastric and SW620 colon cancer cells fall within the parameters of the National Cancer Institute (NCI) [ 49 , 50 ] for plant extracts to be considered promising in the preliminary assay, further studies on mechanisms of action are needed.…”
Section: Resultsmentioning
confidence: 93%
“…Biological assays indicated that chinensinaphthol methyl ether exhibited antiplatelet, antitumor, and antiviral activities [28]. Justicidin B, an arylnaphthalen lignan, was calculated to be a large quantity (0.30 mg/g), which was famous for its wide array of biological properties ranges from cytotoxic to antifungal, antiviral, and antibacterial activities [29]. Justicidin C revealed a concentration‐dependent antiplatelet activity on rabbit platelet aggregation induced by arachidonic acid [5], and its content was 0.17 mg/g.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that justicidins have a variety of biological activities, such as neuroprotection ( Gu et al, 2016 ), cytotoxicity ( Hemmati and Seradj, 2016 ), antiviral activity ( Asano et al, 1996 ), and a wide range of anti-tumor effects. As a potential bioactive substance, its cytotoxicity to numerous cells lines has been systematically studied ( He et al, 2012 ; Ilieva et al, 2014 ; Jin et al, 2014 ; Momekov et al, 2014 ; Won et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%